Cloned genes and genetic regulation of anthocyanin biosynthesis in maize, a comparative review - Chachar, Zaid; Lai, RuiQiang; Ahmed, Nazir; Lingling, Ma; Chachar, Sadaruddin; Paker, Najeeba Parre; Qi, YongWen (Frontiers in Plant Science, 2024)
Anthocyanins are plant-based pigments that are primarily present in berries, grapes, purple yam, purple corn and black rice. The research on fruit corn with a high anthocyanin content is not sufficiently extensive. Considering its crucial role in nutrition and health it is vital to conduct further studies on how anthocyanin accumulates in fruit corn and to explore its potential for edible and medicinal purposes. Anthocyanin biosynthesis plays an important role in maize stems (corn). Several beneficial compounds, particularly cyanidin-3-O-glucoside, perlagonidin-3-O-glucoside, peonidin 3-O-glucoside, and their malonylated derivatives have been identified. C1, C2, Pl1, Pl2, Sh2, ZmCOP1 and ZmHY5 harbored functional alleles that played a role in the biosynthesis of anthocyanins in maize. The Sh2 gene in maize regulates sugar-to-starch conversion, thereby influencing kernel quality and nutritional content. ZmCOP1 and ZmHY5 are key regulatory genes in maize that control light responses and photomorphogenesis. This review concludes the molecular identification of all the genes encoding structural enzymes of the anthocyanin pathway in maize by describing the cloning and characterization of these genes. Our study presents important new understandings of the molecular processes behind the manufacture of anthocyanins in maize, which will contribute to the development of genetically modified variants of the crop with increased color and possible health advantages.